AI as a Study Partner: Exploring Homework Practices, Challenges, and Potentials Among Non-EFL University Students - Yunika Triana; Dewi Zulaiha (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
The rapid integration of generative Artificial Intelligence (AI) in higher education has created a new landscape filled with both opportunities and challenges, especially in the context of language learning. While AI offers undeniable convenience for English language tasks, its independent use creates significant ethical and pedagogical dilemmas. This study, therefore, aims to explore these challenges and the potential of AI in completing English language course homework. This case study utilized semi-structured interviews and thematic analysis to describe and explain the revealed duality in the role of AI. The research reveals a duality in the role of AI. As a positive catalyst, AI serves as an effective cognitive assistant, providing ideational frameworks, initial concepts, and instant feedback that empower students to learn independently (self-directed learning). However, as a source of challenges, AI has been shown to produce biased and inaccurate data, and its unwise use raises serious ethical issues. These issues extend beyond plagiarism to include the erosion of critical thinking skills and a decline in intellectual originality when students use it indiscriminately as a substitute for cognitive effort. This study recommends using AI as a tool for self-learning, but it is necessary to limit students' use of AI. Furthermore, institutions are recommended to adapt AI but need to strengthen students’ digital literacy through structured AI usage guidelines.